DISCOURSE MARKERS AS COGNITIVE REGULATORS OF SOCIAL COMMUNICATION - Michael Vasilyevich Kamensky (Вестник Северо-Кавказского федерального университета, 2022)
In the article the author draws conclusions from the cognitive research of discourse markers and dwells on the peculiarities of their usage in different types of discourse and communicative situations, as well as their relation to the modal / factual properties of discourse.